Pengaruh Model Pembelajaran Berbasis Masalah Berorientasi Socio-Scientific Issue Terhadap Keterampilan Pemecahan Masalah Ditinjau dari Kemampuan Akademik Siswa Pada Pembelajaran Biologi - Kurniawan, Muhammad; Palennari, Muhiddin; Jamaluddin, Asham Bin (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This study aims to determine problem-solving skills through the application of socio-scientific issue-oriented problem-based learning reviewed from the academic abilities of grade X students and to find the interaction of the application of socio-scientific issue-oriented problem-based learning with academic ability on the biology problem-solving skills of grade X students. This research is a quasi-experimental design. The research design used is Pretest-Posttest Non-Equivalent Control Group Design. The population of this study is Class X of SMA Negeri 1 Wonomulyo which consists of five classes, namely Classes X1 to X5 with the research samples used, namely Classes X3 and X6. The data collection technique uses eight-number essay questions that are arranged using problem-solving skill indicators that have been validated by expert validators. The data was analyzed using descriptive and inferential statistical techniques. The results of the study showed that (i) The average score of students who were taught with the SSI-oriented PBL model with a score of 74.38 (ii) The scoring criteria obtained from problem-solving skills are in the good category. (iii) The problem-solving skills of students who were taught with the SSI-oriented PBL learning model on high academic ability obtained an average score of 81.88 and students with low academic ability had an average score of 64.82. (iv).There was no effect of interaction between the model and academic ability on problem-solving skills. The conclusion of this research is that the problem-based learning model oriented towards socio-scientific issues has an effect on students' problem solving skills.